Dispute Resolution for Islamic Banks in Indonesia - Puneri, Atharyanshah (International Journal of Islamic Economics and Finance (IJIEF), 2021)
The rapid growth of Islamic banking and finance industry demanded an improvement in term of standards, frameworks, policy, technologies, resources, and guidelines in order to go beyond without compromising the core values of Islam itself. In the context of legal framework of Islamic banking and finance, it is most likely this industry needs to be highly regulated in order to avoid manipulation and abuse by the irresponsible parties. One of the crucial issue in the area of Islamic Banks in Indonesia is regarding about the dispute resolution mechanism for Islamic Banks. Based on Indonesian positive law, there are two alternative dispute resolution mechanisms that can be exercised by parties to settle disputes in cases involving Islamic Financial Institutions (IFIs) namely through litigation or non-litigation. Litigation comes under the jurisdiction of the Religious Court. Researcher in this study are look deeper into the dispute resolution mechanism for Islamic Banks in Indonesia, as well as going through some decided cases. And based on the study done, it was found that alternative dispute resolution mechanism is more effective to resolve Islamic Banks dispute rather than litigation. In the future, researchers may conduct more research to examine deeper about the dispute resolution mechanism for the whole Islamic Economics and Finance in Indonesia. Moreover, researchers need to look at the regulators' and legislators’ perception towards dispute resolution and legal environment.